2014
DOI: 10.3390/molecules191016013
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic Extract of Taheebo Attenuates Increase in Body Weight and Fatty Liver in Mice Fed a High-Fat Diet

Abstract: Abstract:We evaluated whether intake of an ethanolic extract of Taheebo (TBE) from Tabebuia avellanedae protects against body weight increase and fat accumulation in mice with high-fat diet (HFD)-induced obesity. Four-week old male C57BL/6 mice were fed a HFD (25% fat, w/w) for 11 weeks. The diet of control (HFD) mice was supplemented with vehicle (0.5% sodium carboxymethyl cellulose by gavage); the diet of experimental (TBE) mice was supplemented with TBE (150 mg/kg body weight/day by gavage). Mice administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…(Table 4), there were an increase in females weight group, which were given barley and wheat flour paste, and the males group was not significant differences compared with control group. While, groups 5 & 6 there were no significant differences by consumption barly flour only Table 4.The role of barley in an increasing the weight may be due the nature of the functional ingredients contained which lead to obesity as presented by (9). The result was shown that the barley works as appetizer and incease the intake of food and its play an important role in the incidence of obesity in both sex and regulates the body weight through different mechanisms and reduced energy spending as pointed by (21).…”
Section: Laboratory Animalsmentioning
confidence: 86%
See 1 more Smart Citation
“…(Table 4), there were an increase in females weight group, which were given barley and wheat flour paste, and the males group was not significant differences compared with control group. While, groups 5 & 6 there were no significant differences by consumption barly flour only Table 4.The role of barley in an increasing the weight may be due the nature of the functional ingredients contained which lead to obesity as presented by (9). The result was shown that the barley works as appetizer and incease the intake of food and its play an important role in the incidence of obesity in both sex and regulates the body weight through different mechanisms and reduced energy spending as pointed by (21).…”
Section: Laboratory Animalsmentioning
confidence: 86%
“…The effect of barley on blood glucose in male and female mice after two weeks. Table 6, was noted that the barley has an effect on red blood cells and hemoglobin in groups given barley or (barley & wheat flour) paste, due to the presence of proteins in sufficient amounts of barley that helps the blood system to produce important components (9). Also the results were shown decreasing in a number of platelets after given the groups both paste (barley only or barley-wheat) paste, that may be due to the detect in bone marrow or deficiency resulting from break in the platelets after leaving the bone marrow and pass through the blood vessels to spleen and sticking together with active molecules of barley thus make it a strange body for the immune system that led to attack and the hemolysis (21).…”
Section: Determination the Blood Glucose Levelmentioning
confidence: 99%
“…Taken together, our findings suggest that TWE will be an excellent natural product to help ameliorate the symptoms of various inflammatory immune disorders such as IBD. Very recently, Choi et al reported that the intake of TWE could reduce the development of high-fat diet-induced obesity [ 39 ]. Because obesity is closely linked to macrophage activation, our present findings might provide experimental evidence that TWE treatment can help maintain the homeostasis of metabolic diseases, including obesity and diabetes, by switching macrophage polarization from M1 to M2 phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous investigation, we found several anti-inflammatory cyclopentene derivatives from the water extract of the inner bark of T. avellanedae [12]. Thus, further separation of the water extract was carried out to isolate more active constituents, and resulted in eight new iridoid esters (1)(2)(3)(4)(5)(6)(7)(8). Herein, we report the isolation and characterization of the new compounds together with their anti-inflammatory activity against an LPS-stimulated RAW 264.7 cell line.…”
Section: Introductionmentioning
confidence: 92%
“…Tabebuia avellanedae Lorentz ex Griseb (family: Bignoniaceae) is an evergreen tree, widespread in tropical rain forests throughout Central and South America, and is traditionally used for various ethnopharmacological applications [1]. The biologically active components in T. avellanedae have been reported to have anti-inflammatory [2], antioxidant [3], antimicrobial [4], anticancer [5], antiobesity [6], antidepressant-like [7], and mosquito larvicidal activities [8]. The bioactive chemicals of T. avellanedae inner bark were isolated, including anthraquinones, naphthoquinones, iridoids, coumarins, flavonoids, benzaldehyde derivatives, and benzoic acid derivatives [1].…”
Section: Introductionmentioning
confidence: 99%